Literature Review on the Impact of Ethical Leadership on Employee Performance and Engagement - Martinus Maudy Marsaka; Tobias Krisatianto; Siahaan, Theo Rizaldy (Proceedings of the International Conference on Entrepreneurship (IConEnt), 2024)
The literature review in this study is to determine how ethical leadership will affect employee performance. Ethical leadership has an understanding that emphasizes ethics, morality, and the integrity of every action to be taken, both in terms of interactions with employees and in making decisions. Leaders who possess ethics, morality, and integrity will set an example of wise behavior that can serve as a foundation for building an organizational culture in accordance with good ethics and norms. This research will use the library method, which involves studying and analyzing information from books, scientific journals, and other scholarly works as supporting materials. From the reviewed journal, one will understand the role of ethical leadership that impacts employee performance and engagement. The results of this study will show that leadership prioritizing ethics will affect employee performance. This is because employees feel respected and valued by their superiors while working, which will increase their work productivity. This finding can also serve as a recommendation for organizations that want to improve employee performance by implementing ethical leadership.